Aplikasi Penyandian Record Menggunakan Metode Twofish - Asmawi (JUKI : Jurnal Komputer dan Informatika, 2020)
Technological developments are increasingly progressing, for example for data security. Data security is very important in maintaining the confidentiality of information, especially sensitive information, which only authorized parties can know, moreover data storage is done on a computer, if the data is not secured in advance then the data will be known by the parties who are entitled to it. is not entitled to the security of data on the record, the data on the computer is not easily seen and cannot be changed by irresponsible parties so that the data will be safe and cannot be contested by any party One of the data safeguards is by using a cryptographic system, which is the encryption of the contents of the information (plaintext) into incomprehensible content through an encryption process (encoding) and to retrieve the original information, a description process (deschiper) is carried out accompanied by using the correct key. Data encryption or cryptography is the study of hiding letters or writings so that they cannot be read by unauthorized people. Cryptography has been used since the time of Julius Caesar, who sent messages to the commander but did not have a courier to carry the message. Cryptography has 2 (two) important parts, namely encryption and description. Encryption is the process of encrypting the original message into a message that cannot be interpreted as the original. Description is to change a message that has been interpreted to be the original message, usually called plaintext, while the message that has been interpreted is called ciphertext.